Acute Disseminated Encephalomyelitis Secondary to Mycoplasma pneumoniae Infection Mimicking Extrapyramidal Symptoms: A Case Report - Cheng, Chih-Chieh; Fan, Hueng-Chuen; Chi, Ching-Shiang; Lee, Chuen-Ming; Huang, Shih-Ting; Yeh, Lang-Lung (Journal of Pediatric Neurology, 2018)
Acute disseminated encephalomyelitis (ADEM) is a rare disease affecting the central nervous system (CNS), and it is difficult to diagnose clinically because of vague prodromal presentations. The therapeutic aim for ADEM is to inhibit the CNS inflammatory reaction as quickly as possible. Treatments may include high-dose corticosteroids and anti-inflammatory and immunosuppressant therapies such as plasmapheresis and high-dose intravenous immunoglobulin. ADEM usually has a good prognosis. Here, we report a rare case of ADEM secondary to Mycoplasma pneumoniae infection mimicking extrapyramidal symptoms.
Keywords: acute disseminated encephalomyelitis; Mycoplasma pneumoniae; extrapyramidal symptoms